Formulasi dan Evaluasi Granul Gastroretentive Mukoadhesif Amoksisilin - Hamsinah Hamsinah; Jufri Jufri; Ermina Pakki (Universitas Islam Negeri Alauddin Makassar, 2016)
Amoxicillin is a semisynthetic antibiotic, belonging to the β-Lactam family, which is effective for bacterial infection treatment, especially for Helicobacter pylori infection. In this research, Amoxicillin was formulated as mucoadhesive granules dosage form to improve their effectivenesses by increasing the residence time of dosage form in the stomach. Mucoadhesive granules were prepared by wet granulation method in ten formulas using HidroxypropylMethyl cellulose, Methyl cellulose and Ethyl cellulose as mucoadhesive polymers. Granules were evaluated for moisture content, flow rate, angle of repose, density, mucoadhesive strength with wash off test, and dissolution.The results of this researchshowed that formula IB with 50% HPMC has best mucoadhesive strength with percentage of mucoadhesion 20% in 90 minutes of wash off test, and also formula IB is slowest formula in releasing of drug, with percentage of drug released is 55,76% in 15 minutes and 104,01% in 180 minutes.